Purificação e caracterização da endo-oligopeptidase-A de membranas do cérebro humano - Furtado, Katia Machado da Silveira (1990)
From the membranes of human brain,the endo- ol igopept idase - A was purified close to homogeneity, introducing the following steps of purification. a) homogeneization with water in the proportion of 1:4 (W/V) ■, b) centrifugation at 25,000 G.,during 60 min; c) cromatography in DEAE-cel1ulose; and d) preparative electrophoresis in poliacri1amide gel. After purification, the enzyme was submitted to plate electrophoresis without S.D.S., resulting in the appearance of a band of protein,with a light contaminant. The purified enzyme showed the following properties: PH near to neutrality; isoelectric point of 5.36; molecular weight of 70,000 daltons; inihibited by cátions Cu++, Zn++, Ni++, Co++,Ca++ and Fe++; inihibited by PMAC and PMSF; not inihibited by EDTA and orthophenanthralene; has a reactivation with B - mercaptoethanol. The membranous endo-oligopeptidade - A released MET and LEU-enkephalins from the opioid peptides, such as: Dinorphin 1-8; MET-enkepha1in-ARG-GLI-LEU-LIS; Octapeptide, BAM 12; B-Neo- endorphin and B-Dinorphin. However, it did not liberate enkephalins